Cognitive Rehabilitation of Episodic Memory Disorders: From Theory to Practice - Ptak, Radek; Van Der Linden, Martial; Schnider, Armin (Frontiers in Human Neuroscience, 2010)
Memory disorders are among the most frequent and most debilitating cognitive impairments following acquired brain damage. Cognitive remediation strategies attempt to restore lost memory capacity, provide compensatory techniques or teach the use of external memory aids. Memory rehabilitation has strongly been influenced by memory theory, and the interaction between both has stimulated the development of techniques such as spaced retrieval, vanishing cues or errorless learning. These techniques partly rely on implicit memory and therefore enable even patients with dense amnesia to acquire new information. However, knowledge acquired in this way is often strongly domain-specific and inflexible. In addition, individual patients with amnesia respond differently to distinct interventions. The factors underlying these differences have not yet been identified. Behavioural management of memory failures therefore often relies on a careful description of environmental factors and measurement of associated behavioural disorders such as unawareness of memory failures. The current evidence suggests that patients with less severe disorders benefit from self-management techniques and mnemonics whereas rehabilitation of severely amnesic patients should focus on behaviour management, the transmission of domain-specific knowledge through implicit memory processes and the compensation for memory deficits with memory aids.